2011
DOI: 10.1002/app.34515
|View full text |Cite
|
Sign up to set email alerts
|

Diazotization–azidation of amines in water by using crosslinked poly(4‐vinylpyridine)‐supported azide ion

Abstract: The use of polymeric reagents simplifies routine azidation of diazonium salts, because it eliminates the traditional purification. An efficient, simple, and effective method for the preparation of aryl azides is described. The synthesis of aromatic azides from the corresponding amines is accomplished under mild conditions with sodium nitrite in the presence of p-toluenesulfonic acid or concentrated H 2 SO 4 at low temperature (0-5 C to room temperature). The obtained relatively stable diazonium salts, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…It is important to note that this polymeric reagent was stable and could be stored for a long time (months) without losing its activity; it could be readily used for the diazotization–cyanation of anilines. [P 4 ‐VP]I was recently prepared and used for the preparation of other functionalized polymers, including polymer‐supported thiocyanate, polymer‐supported carboxylate, polymer‐supported potassium ferrate, polymer‐supported azide ion,51 and polymer‐supported nitrite ion 46–50. Although [P 4 ‐VP]I is well known, [P 4 ‐VP]CN was used the first procedure for the direct diazotization–cyanation of aryl amines, and on the basis of our knowledge, there has been no report in the literature on the synthesis of aryl nitriles based on polymer‐supported cyanide ion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that this polymeric reagent was stable and could be stored for a long time (months) without losing its activity; it could be readily used for the diazotization–cyanation of anilines. [P 4 ‐VP]I was recently prepared and used for the preparation of other functionalized polymers, including polymer‐supported thiocyanate, polymer‐supported carboxylate, polymer‐supported potassium ferrate, polymer‐supported azide ion,51 and polymer‐supported nitrite ion 46–50. Although [P 4 ‐VP]I is well known, [P 4 ‐VP]CN was used the first procedure for the direct diazotization–cyanation of aryl amines, and on the basis of our knowledge, there has been no report in the literature on the synthesis of aryl nitriles based on polymer‐supported cyanide ion.…”
Section: Resultsmentioning
confidence: 99%
“…Although polymer‐supported reagents, especially anion‐exchange resins, have been widely applied in organic synthesis,34–52 to the best of our knowledge, there has been no report on the synthesis of aryl nitriles via a dediazoniation–cyanation reaction based on polymer‐supported cyanide ions. Very recently Harrison and Hodge52 reported the synthesis of alkyl nitriles from alkyl halides with the Amberlyst A 26 CN − form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regioselective ring opening of polycyclic aromatic hydrocarbon epoxides by this polymer also reported by Lakshman et al60 Blass et al reported a one‐pot, two step preparation of functionalized 1,2,3‐triazoles by Merrifield resin supported ammonium azide anion 61. The 1,3‐dipolar cycloaddition by using poly (ethylene glycol)‐supported azide is also reported by Molteni et al62 Previously, we have also prepared crosslinked poly (4‐vinylpyridine)‐supported azide ion, [P 4 ‐VP]N 3 , and used for synthesis of alkyl azides from alkyl halides,56 diazotization‐azidation of amines in water57 and [2 + 3] cycloaddition reaction of azide ion with nitriles 58…”
Section: Introductionmentioning
confidence: 60%
“…Although polymer‐supported reagents especially anion exchange resins have been widely applied in organic synthesis,46–62 a literature search shows that there are a few reports in organic transformation based on polymer supported azide reagent. Brenelli et al reported that Amberlite IRA 900 supported azide resin is a highly effective reagent for the conversion of α‐haloketones into α‐azidoketones 59.…”
Section: Introductionmentioning
confidence: 99%